The manifestation of justice in ancient Egyptian law, with specific reference to The tale of the eloquent peasant - Blerk, N. J. Van (Journal for semitics, 2010)
Justice (mα'αt) governed the lives of ancient Egyptians because they saw no difference between divine and human justice. In this article I focus on whether law and a functional legal system (hpw) existed in ancient Egypt. I explore the importance of law for the ancient Egyptian society, which had a high reputation for justice, and discuss what the ancient Egyptians understood by the terms hp/hpw. Law was essential for them and was not merely earthly hpw, but also the divine law, M3't. I indicate that there is abundant evidence of written law in Egypt and they must have had a functional legal system. I discuss terms used in the Tale of the eloquent peasant relating to justice and law and evaluate it as a source of information about ancient Egyptian law and the principles of law and justice in that era. This important work has a strong legal background and shows the interaction between law and justice.